A Development of Homolog Sequence of Eimeria tenella Partial Genome as a Probe for Molecular Diagnosis of Coccidiosis - S, Sumartono (Universitas Gadjah Mada, 2005)
The goal of the research was to develop a homolog sequence of Eimeria tenella partial genome as a molecularprobe for diagnose coccidiosis using dot blot method. A probe of homolog sequence of E.tenella partial genomeand a non radioactive label, dig-11-dUTP, were used for this research. Four concentrations of molecular probelabeled with dig-11-dUTP, namely, 158,33 pg/μl, 52,25 pg/μl, 15,83 pg/μl and 5,225 pg/μl were tested to detect0,6551 μg DNA target. The procedure of labeling and hybridization detection between DNA target with themolecular probe labeled with dig-11-dUTP were carried out with Digh high prime DNA labeling and detectionstarter Kit I. The conclusion of the research was that 52,25 pg/μl molecular probe or more which its sequenceGGCA CAGTATCCTCCTTCAGGGCAGGG CTCGCACTGGTCAAA CGCGG TAC CATT could detect DNAtarget by dot blot method.Keywords: coccidiosis, E. tenella genome, molecular probe, dot blot hybridization